Unemployment in the Polish countryside and its effect on the development and rate of maturation of rural girls - Olszewska, Elżbieta; Łaska-Mierzejewska, Teresa (Anthropological Review, 2008)
The aim of this study is to assess the biological status of girls from landless rural families - daughters of working fathers, and those of unemployed fathers. The measures include age at menarche, body height and weight, and the body mass index (BMI). The study of rural girls was conducted in 2001; a total of 9599 girls aged 9-18 were examined. The material used in the present article only embraces girls from non-farming rural families (N = 4476). It was divided into daughters of working fathers (86.5%) and those of unemployed fathers (13.5%). Daughters of working fathers mature earlier than those of unemployed fathers. The difference in the age at menarche is 0.39 years and is statistically significant. The age at menarche of daughters of unemployed fathers approximates the menarchal age of daughters from farming families with many children (5 or more) in which both parents have elementary education. In groups similar in terms of the father's education and the number of children in the family, daughters of unemployed fathers display a later age at menarche and a lower body height and weight. These results support the statement that a father's lack of employment affects the biological status of his daughters.